PENGARUH PERSEPSI RISIKO, LITERASI KEUANGAN, GAYA HIDUP, DAN FAKTOR SOSIAL TERHADAP MINAT MAHASISWA MENGGUNAKAN PINJAMAN ONLINE - Lumbanraja, Riska Hasnah; Turnip, Angel Aulia; Br Sinaga, Jholant Bringg Luck Amelia; Marini, Yushita (JURNAL LENTERA BISNIS, 2026)
This quantitative study aims to analyze the influence of risk perception, financial literacy, lifestyle, and social factors on students' interest in using online loan services. The study subjects consisted of 100 active students of the Faculty of Economics, in their fourth semester and above, in Medan City, selected based on criteria. Data were collected using a Likert-scale questionnaire and processed using IBM SPSS Statistics. The results of the study partially indicate that risk perception has no effect on interest in use, while financial literacy, lifestyle, and social factors have a significant influence. Simultaneously, all of these independent variables influence students' interest in using online loans.